'My brain hurts:' incorporating learner interests into the classroom. (2nd January 2019) - Tadic, Nadja
ABSTRACT: Educators have long been advocating for the appropriation of students' interests into the classroom as a means of promoting participation and learning. However, little attention has been paid to the possible issues that interest-driven pedagogy might engender for both teachers and students through its blend of the personal and academic. This article examines how one elementary school teacher appropriates his students' interests into an instructional task and how this attempt at blending real-life and instruction shapes student participation and task completion. The data come from an hour-long video recording of a third-grade sheltered instruction English Language Arts class at a public school in the United States. Conducted within the conversation analytic framework, the study shows that implementing interest-driven pedagogy in the classroom can engender a struggle between instructional task demands and real-life student concerns, consequently both hindering and facilitating student participation and task completion.